Práticas sustentáveis e o impacto no desempenho de pequenas propriedades cafeeiras - Carvalho, Adriele Talita (2021)
Due to the increasingly competitive market, the demand of consumers and customers to acquire high quality and sustainably produced coffees has been growing. Small coffee producers that aim to supply this market can resort to adopting sustainable practices established by socio-environmental certifications. The process of adopting such practices becomes more viable, especially for small producers, when they join Cooperatives. Cooperatives, especially the most developed ones, encourage and disseminate sustainable practices to all their members, whether they are certified or not. There is a research gap on what impacts sustainable practices have on the performance of small coffee farms. This dissertation aims to analyze whether the practices of environmental sustainability, management and economic sustainability impact the economic performance and welfare of the producer and the performance in productivity and quality of small coffee properties located in the southern region of Minas Gerais. A systematic literature review was carried out in order to develop a robust theoretical basis on the topic, and a total of 64 articles were selected and analyzed. Then, an empirical research was developed through a survey and the data were analyzed with the statistical technique Structural Equation Modeling (SEM) in a sample of 60 small coffee producers. The most relevant relationship was the impact of management practices and economic sustainability on the economic performance and well-being of the producer. This dissertation provides contributions to the literature by presenting an up-to-date overview of the subject, and to the knowledge of professionals in the field by presenting suggestions on which sustainable practices should be encouraged to improve the performance of small coffee farms.